The Notion of Regulation in Internacional Law - Olcese, Tomás; Miranda, Luiz Ricardo (Latin American Journal of Trade Policy, 2019)
Regulation – a notion first borrowed from the natural sciences by economists and then from economists by lawyers – has become increasingly common in international law. Within this article, we attempt to define the main features of international regulation. To do so, we will retrace, although not exhaustively, the path of the successive applications of this notion through its implementation in two major legal models. This will be a necessary step in defining its distinctive criteria. Thereafter, we will analyze the feasibility of employing these criteria into international regulation to determine whether the phenomenon observed within domestic legal systems is actually the same phenomenon or a completely different one.